The Effectiveness of Cognitive Behavior Therapy Counseling to Reduce Bullying Behavior - Sa'adah, Sa'adah; Eddy Wibowo, Mungin; Sunawan, Sunawan (Universitas Negeri Semarang, 2021)
Schools play an important role in shaping and developing the potentials of students, in developing the potentials of students, it is necessary to create an attractive, safe, comfortable, and conducive school climate so that learning objectives are achieved, but unfortunately the rampant behaviour of bullying causes the classroom climate to be unsatisfactory. conducive and cause problems. The purpose of this study was to test the effectiveness of Cognitive Behavior Therapy (CBT) counselling to reduce bullying behaviour in students of SMP Negeri 2 Angsana. This study used the Single-Subject Design (SSD) method with multiple baseline cross-variable patterns conducted in 11 observation sessions consisting of 3 baseline A1 sessions, 6 intervention sessions and 3 baseline A2 sessions. In conducting observations, researchers used the Goal Attainment Scaling (GAS) instrument and analyzed using visual charts. The results showed that Cognitive Behavior Therapy (CBT) counselling was able to reduce bullying behaviour